N, N-Dimethylformamide-stabilized copper nanoparticles as a catalyst precursor for Sonogashira–Hagihara cross coupling. Issue 37 (26th April 2017) - Oka, Hideo; Kitai, Katsuya; Suzuki, Takeyuki; Obora, Yasushi
Abstract : We found that DMF-stabilized Cu NPs have high catalytic activity in the Sonogashira cross-coupling reaction at low catalyst loadings (0.2 mol%). Abstract : We report the catalysis of a Sonogashira–Hagihara cross-coupling reaction using a DMF-stabilized copper nanoparticle catalyst. The reaction proceeded with low catalyst loadings, and a turnover number of 4.0 × 10 3 was recorded for 0.01 mol% catalyst loading. DMF-stabilized copper nanoparticles thus showed high catalytic activity.